1996
DOI: 10.1128/mcb.16.10.5557
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Seven Hydrophobic Clusters in GCN4 Making Redundant Contributions to Transcriptional Activation

Abstract: GCN4 is a transcriptional activator in the bZIP family that regulates amino acid biosynthetic genes in the yeast Saccharomyces cerevisiae. The N-terminal 100 amino acids of GCN4 contains a potent activation function that confers high-level transcription in the absence of the centrally located acidic activation domain (CAAD) delineated in previous studies. To identify specific amino acids important for activation by the N-terminal domain, we mutagenized a GCN4 allele lacking the CAAD and screened alleles in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
97
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 72 publications
13
97
0
Order By: Relevance
“…Thus, although Gcn4 appears to make multiple, low affinity interactions with several Gal11 regions, Pdr1 and Oaf1 interact more tightly, and perhaps exclusively, with the KIX domain. This view is consistent with our previous finding that the Gcn4 activation domain has a random coil structure in solution (63) and contains seven different clusters of hydrophobic residues scattered throughout the acidic activation domain, whose functions in Gcn4-Mediator interactions and transcriptional activation are highly redundant (47,61,62).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, although Gcn4 appears to make multiple, low affinity interactions with several Gal11 regions, Pdr1 and Oaf1 interact more tightly, and perhaps exclusively, with the KIX domain. This view is consistent with our previous finding that the Gcn4 activation domain has a random coil structure in solution (63) and contains seven different clusters of hydrophobic residues scattered throughout the acidic activation domain, whose functions in Gcn4-Mediator interactions and transcriptional activation are highly redundant (47,61,62).…”
Section: Discussionsupporting
confidence: 81%
“…Supporting the conclusion that Gal11 contains independently functioning interaction modules, we found that distinct recombinant Gal11 polypeptides containing the KIX domain, a region altered by ⌬5 and the WQV substitution, and a region encompassing ⌬8 all bind to recombinant Gcn4 in vitro in a manner enhanced by the hydrophobic residues in Gcn4 necessary for Mediator binding to Gcn4 in vitro and transcriptional activation by Gcn4 in vivo (47,61,62). Furthermore, we used NMR chemical shift mapping to provide evidence that the recombinant Gcn4 activation domain interacts specifically with the KIX domain in solution, contacting a surface that overlaps with, but is distinct from, surfaces contacted by segments of other yeast or mammalian activation domains.…”
Section: Discussionmentioning
confidence: 48%
“…In yeast, GCN4 and VP16 require different mediator subunits for activated transcription of specific genes (Myers et al, 1999). This suggests that the TADs of GCN4 and VP16, both of which are acidic, may operate by different mechanisms and interact with overlapping but nonidentical spectra of downstream targets (Jackson et al, 1996). The TADs of GCN4 and of VP16 also interact with the chromatin remodeling complex SWI/SNF (Liberati et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Gcn4p to interact with coactivators in cell extracts (16,17) and to recruit coactivators to target promoters in vivo (14,18) depends on the hydrophobic clusters in its activation domain required for transcriptional activation in vivo (19). To determine whether recruitment of ArgR͞Mcm1p by Gcn4p involves its activation domain, we conducted ChIP assays on isogenic strains expressing wild-type Gcn4p or a mutant harboring Ala substitutions in all seven hydrophobic clusters in the activation domain (gcn4-14Ala).…”
Section: Gcn4p Recruits the Entire Argr͞mcm1p Complex To Arg1 In Argimentioning
confidence: 99%